RED PALM WEEVIL, Rhynchophorus ferrugineus (Olivier, 1970) - CURRENT SITUATION IN HERZEGOVINA TWO YEARS AFTER THE FIRST FINDING - Ostojić, Ivan; Zovko, Mladen; Jurković, Dragan (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
The red palm weevil Rhynchophorus ferrugineus (Olivier, 1970) is a new invasive species in Bosnia and Herzegovina. It is known worldwide as an extremely dangerous pest of palm trees, which can completely destroy them. Red palm weevil originates from Southeastern Asia, but over the last three decades, it has also spread to Mediterranean and now is a major insect pest of palms in this region. In B&H, the red palm weevil was first recorded on Phoenix canariensis in 2019 in city of Čapljina and on few localities in Neum (Herzegovina-Neretva Canton). Two years after the first findings in the town of Čapljina, five canary date palms were identified with symptoms of red palm weevil infection, but not a single palm tree has been cut down. After visual inspection of canary date palm trees in Neum, two years after the first findings, many of them showed symptoms of infection and 22 canary date palm have been eradicated.